Tuvalu Early Grade Reading Assessment : Results Report - World Bank (World Bank, Washington, DC, 2019)
This report summarizes the results of an Early Grade Reading Assessment (EGRA) conducted in Tuvalu from September 21 and October 27, 2016. With funding from the Global Partnership for Education, the World Bank and Education Technology for Development (Et4d) carried out the assessment in collaboration with the Tuvaluan Ministry of Education, Youth and Sports (MEYS). The overall purpose of the EGRA was to inform education policymakers of students’ basic reading skills in years 1-3 of primary school and to identify factors that contribute to language development in Tuvalu. The findings are expected to assist policymakers with designing effective early grade reading interventions to improve school performance and literacy outcomes in Tuvalu. This activity is part of the Pacific Early Age and Readiness Program (PEARL), which was established to improve the school readiness and literacy outcomes of children throughout the Pacific region. The report is divided into six chapters beginning with this introductory section in chapter. Chapter two will discuss the TuEGRA survey design and implementation. Chapter three presents overall results of the reading assessment per sub-test, gender and year as well as a summary of the overall strengths and weaknesses responding to questions 1, 4 and 5. The correlation between oral reading fluency and comprehension (question 2) is discussed in chapter four. As there are no established standards for reading fluency, the report used 80 percent reading comprehension benchmark as the basis for determining fluency scores. Chapter five provides an analysis of student and teacher factors associated with improved reading outcomes, which corresponds with question 6 (6a, 6b, and 6c). Finally, the conclusions and policy recommendations to improve literacy outcomes are presented in chapter six.